2005
DOI: 10.3846/16486897.2005.9636846
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Road Maintenance Salts on Water Ecosystems According to Diatom Flora Investigation

Abstract: Road maintenance chlorides have a negative environmental impact. Chemical solutions of melting snow inevitably get into the soil and change its chemical composition. They also get into ponds. Five water basins in Vilnius city, at 5–80 m from roads, were chosen for investigation. The highest chloride concentrations were established by roads where winter road maintenance is performance at the highest level. The hydrophysical and chemical parameters of the investigated lakes depend on anthropogenic processes. Dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 3 publications
0
3
0
3
Order By: Relevance
“…Seeking to determine a negative effect of technical salts on the ecosystems in the environment of roads, Department of Environment Protection of Vilnius Gediminas Technical University investigated the impact of road maintenance salts on water ecosystems according to diatom flora investigation in the Verkiai pond and the Gineitiškiai lake in 2004. The investigation findings show that one of the reasons that could impact on the spread of diatom flora typical to salty waters is road maintenance salts (chlorides) [2].…”
Section: Introductionmentioning
confidence: 94%
“…Seeking to determine a negative effect of technical salts on the ecosystems in the environment of roads, Department of Environment Protection of Vilnius Gediminas Technical University investigated the impact of road maintenance salts on water ecosystems according to diatom flora investigation in the Verkiai pond and the Gineitiškiai lake in 2004. The investigation findings show that one of the reasons that could impact on the spread of diatom flora typical to salty waters is road maintenance salts (chlorides) [2].…”
Section: Introductionmentioning
confidence: 94%
“…Few studies have examined the toxicity of road salts to phytoplankton (Evans & Frick, 2001). Patrick et al, (1968) observed a 50% decrease in the cell numbers of the diatom Nitzschia linearis when exposed to 2.43 g/L of NaCl (1.48 g/L of Cl − ) for 120 h. Oškinis and Kasperovičius (2005) studied the impacts of deicers (75‒3120 mg/L of Cl − ) on diatom flora at five ponds located 5‒80 m from roads. They concluded that salt affected diversity and abundance of the diatom communities (Oškinis & Kasperovičius, 2005).…”
Section: Impacts Of Deicers On Aquatic Resourcesmentioning
confidence: 99%
“…Atliekant žolinės augmenijos antžeminės dalies aukščio tyrimus, pastebėta, kad druskos kiekis ištirpusiame sniege turi tiesioginės įtakos pakelės augmenijos antžeminės dalies aukščiui: kuo didesnė NaCl koncentracija, tuo antžeminė dalis žemesnė [1][2][3][4][5][6][7][8][9][10][11].…”
Section: įVadasunclassified
“…Skaičiuojant antžeminės dalies aukštį (cm) pagal sumodeliuotą lygtį, pirmosios savaitės rezultatai labiausiai neatitiko tikrojo antžeminės dalies aukščio (cm) (iki 83,53 %). 4. Mažiausios tikrojo ir apskaičiuotojo antžeminės dalies aukščio (cm) paklaidos nustatytos tiriant miglę (11,40 % kontrolinių ir 12,32 % 1 g/kg NaCl koncentracijos dirvožemyje), didžiausios -eraičiną (26,19 % kontrolinių ir 28,10 % 1 g/kg NaCl koncentracijos dirvožemyje).…”
Section: Išvadosunclassified